2010
DOI: 10.3109/14767058.2010.520047
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and cause of death in a neonatal intensive care unit – How important is autopsy?

Abstract: Despite the high agreement rate between clinical and pathological diagnoses, autopsy frequently added important data, including several cases in which it established the diagnosis or provided information relevant for parental counseling regarding future pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 9 publications
4
22
0
6
Order By: Relevance
“…Eight studies reported the mortality outcomes for all admissions to the NICU ( 20 , 22 , 25 , 33 37 ), five of which examined the age of infants at death ( 20 , 22 , 33 , 34 , 37 ). Musooko et al ( 37 ) noted that 45.9% (17/37) of infants with early neonatal deaths (death within 7 days of birth) and those with severe perinatal morbidity died on the first day of life in Uganda.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies reported the mortality outcomes for all admissions to the NICU ( 20 , 22 , 25 , 33 37 ), five of which examined the age of infants at death ( 20 , 22 , 33 , 34 , 37 ). Musooko et al ( 37 ) noted that 45.9% (17/37) of infants with early neonatal deaths (death within 7 days of birth) and those with severe perinatal morbidity died on the first day of life in Uganda.…”
Section: Resultsmentioning
confidence: 99%
“…Musooko et al ( 37 ) noted that 45.9% (17/37) of infants with early neonatal deaths (death within 7 days of birth) and those with severe perinatal morbidity died on the first day of life in Uganda. The reported median age at death was 4 days in Australia ( 20 ), 4.4 days in Nigeria ( 33 ), and 10.5 days in Portugal ( 34 ). Sankaran et al ( 22 ) found that 75% (596/795) of deceased infants passed away 12 days since NICU admission in Canada (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Costa et al. showed that in a cohort of 110 deceased infants, pathological and clinical diagnoses were in complete agreement in only 34% of cases and that PMs revised cause of death in 24.5% of cases. It is understandably difficult to approach grieving parents and relatives for permission to perform further examination on their deceased infants soon after death, especially when the clinician has little experience and training in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, related to other pathologies, have shown that the necropsy �ndings and histological assessment of the lungs may change the diagnosis in a signi�cant number of cases [14,15].…”
Section: Discussionmentioning
confidence: 98%